TEACHING SKILLS THROUGH THE USE OF AUDIO-VISUAL MEDIA AT MIDDLE SCIENCE TEACHERS IN SUBURBS - Yacob, Fakhri; Daud, Ridwan M (Biotik, 2023)
This research study aims to: 1) design audio-visual media for the teaching and learning process for junior high school science lessons and 2) use audio-visual media modules in the teaching and learning process for junior high school science lessons in suburb areas. The research method used is a type of research and development method or Research and Development (R&D). This research and development model uses stages that have been adapted through the stages of analysis, design, product development, and 4) validation (Borg and Gall, 1983: 772). The development stage begins with the production stage which produces the initial product, then validation is carried out by media experts, technology experts, and material experts and repeated validation after revision. The research data was obtained through instruments in the form of assessment sheets/validation by media experts, technological experts, and material experts which consisted of a number of assessment aspects. This study reports that 1) the design of audio-visual media for the teaching and learning process for junior high school science lessons has a very good level of feasibility (90, 29%) and 2) the module for using audio-visual media also has a very good level of feasibility (91, 14%). This research recommends that audio-visual media designs and audio-visual media use modules can be used in the science teaching and learning process at the junior high school level in suburb areas, especially in the subject of Food Digestion in Humans. Keyword: Research and Development, Audio-visual Media Design, Module Usage